6+4m=-m+-6

Simple and best practice solution for 6+4m=-m+-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+4m=-m+-6 equation:



6+4m=-m+-6
We move all terms to the left:
6+4m-(-m+-6)=0
We add all the numbers together, and all the variables
4m-(-1m-6)+6=0
We get rid of parentheses
4m+1m+6+6=0
We add all the numbers together, and all the variables
5m+12=0
We move all terms containing m to the left, all other terms to the right
5m=-12
m=-12/5
m=-2+2/5

See similar equations:

| 2m-10=100 | | X=36+-0.5y | | 255=40x+15 | | 3x+15=−5x+20 | | 20+0.10=30x | | 2(4x-1)=6x+10 | | -6n-4n=30 | | 4x-3=5x–8 | | 3x+4x-8=2x+7 | | 2x+2.4=5 | | 23=-9+8x | | -9r-4=-84 | | 4/b-2=4/24 | | 13/x=7.76/4 | | 255=x+15 | | 5x=1890 | | a0.9a+4.96=3.6+1.4a | | 2(3x-3)=3(4x+6) | | -156=-13j | | 9i-6i=18 | | x=3/2,-2 | | 4.9b-4=2.9b+12 | | 2x+3x-6=3x+10 | | 21+2z=19 | | .125x=80 | | 2x+3=5x+3–3x | | r+4/10=8 | | 606=f+187 | | (b+9)/2=30 | | c/19+15=18 | | V×2+5v+4=0 | | c19+15=18 |

Equations solver categories